The Role of Happiness on Job Satisfaction and Employee Performance: A Cross-Cultural Research in Italy and Turkey - Erselcan, Recep Caner; Süral Özer, Pınar (International Journal of Contemporary Economics and Administrative Sciences, 2023)
The research aims to analyse the explanatory effects of workplace happiness on employee performance, and discover whether the variables were affected by cultural variations. The Italian sample, taken in July 2017 consisting of 409 responses resulted that "happiness at work" positively affects employee performance, fully mediates between job satisfaction and performance. Besides, job satisfaction indirectly associates performance only through the developer contribution of “happiness at work”. The Turkish sample, taken in January 2018 consisting of 550 responses showed the positive effect of “happiness at work” on employee performance, moderates only by the means of the interaction of job satisfaction and performance. The study provides current validation for the assumption that “Happy employees are more productive at work” and contributes to previous studies suggesting that relationships of variables can be affected by cultural characteristics.